PELATIHAN PENULISAN ARTIKEL ILMIAH PENGABDIAN KEPADA MASYARAKAT - BUDAARSA, KOMANG; WIJAYA, NYOMAN (Buletin Udayana Mengabdi; Vol 6 No 1 (2007): Volume 6 No.1 - April 2007, 2012)
ASBSTRACT Training of writing of sience article of community services have been conducted on 20 October 2006 followed 24 people, from 10 faculty in Udayana University. Target of this training to give skill and knowledge to a number of lecturer specially young lecturer in Udayana University about technique sience article of community services. After training expected by all participant can make real correct and good sience article of community services as according to existing guidance. Training conducted in the form of tutorial for the theory of discussion and, later then continued with direct practice make sience article of community services. Before executed training of participant given pretest which contents concerning writing of sience article of community services. The Tes meant to know how far knowledge and understanding of participant before given items. Result of tes indicate that knowledge of participant before given training is 82 %. Later then after given training become 100 %. Its meaning happened the make-up of understanding and knowledge counted 18% from participant to items the given. Have succeeded to be made 19 title sience article of community services which have followed real correct writing method. The article will be given high priority to be to be loaded in journal of Udayana Mengabdi next edition.